APLIKASI METODA CRITICAL PATH METHOD (CPM) DALAM PENJADWALAN KEGIATAN PEMBANGUNAN PERUMAHAN - Sutanto, Sutanto (Gema Teknologi, 2018)
The development of housing development in Indonesia is now showing a very rapid progress in line with the rate of population growth and the increase in income per capita community, so that housing demand is getting bigger. For that much needed planning and scheduling activities of a good housing development projects in accordance with the progress of science and technology in order to have added value to the implementation of the housing development. The Critical Path Method (CPM) application research in guarding housing development activities and the impact on technical constraints in the field is one solution. Based on the results of data processing shows that the use of scheduling activities of housing development projects with Critical Path Method method has resulted in more added value.